Risk Attribute Analysis and Risk of Adherence to Taking Medication for Pulmonary TB Patients at the Jayapura Regency Office - Hasmi, Hasmi; Makaba, Sarce (Formosa Journal of Science and Technology, 2024)
This study aims to analyze the Risk Attributes and risks of medication adherence in patients with pulmonary TB. Type of survey research designed by cross sectional. A sample of 81 people was taken using the purposive sampling technique. The results of the study were with the variable value of RA = -21%, RP=1(0.19-5.9), gender RA=18%, PR 1.7(0.9-3.3), education RA=-16%, PR =0.57. Work RA = 19%, RP = 2.12 (0.72-6.22). TB MDR RA =62%, RP=16 (5.2-48.4). Side effects  of RA Drug = 30%, PR = 2.5 (1.2-4.88), History of Comorbidities RA = 61%, PR = 3.6(2.02-6.6), duration of treatment RA = 50% PR = 3.8 (2-7). The variable that contributes the most to medication adherence is MDR TB status.